Application of Vanname Shrimp Pond Cultivation Technology Intensive System and Good Fish Farming Method (CBIB) Standards in Majannang Village - Mulyani, Sri; Pallu, Muhammad Saleh; Mardiana, Mardiana; Fikruddin, Muhammad; Yunus, Muhammad Kafrawi; Fatmawati, Fatmawati; Handayani, Hainun Putri; Ningsi, Sitti Warda (STKIP Singkawang, 2024)
PT. Bosowa Isuma which has problems with suboptimal shrimp pond productivity (traditional aquaculture system), water quality monitoring is still manual, manual feeding, and does not understand the standards of Good Fish Farming Methods (CBIB). The goal of kedaireka 2022 is to improve pond governance that is more systematic, productive, environmentally friendly and sustainable and implement the Good Fish Farming Method (CBIB) standard. The implementation method with the application of intensive cultivation system technology and CBIB standards is planted with shrimp covering an area of 5,000 m2 owned by PT. Bosowa Isuma. Vanname shrimp farming in a controlled environment so as to provide food guarantees from cultivation by paying attention to sanitation, shrimp and fish feed and chemicals and biological materials. The executors of the activities are lecturers, technicians of PT. Bosowa Isuma and 7 students of the MBKM. The result of the activity is the application of Vanname shrimp farming technology Intensive System using mill technology, automatic feeder feed and IoT-based monitoring applications is an engineering of sustainable appropriate technology capable of solving the problems of farmers in Majannang Village, especially PT. Bosowa Isuma. Supporting factors in carrying out activities are the availability of land for Vanname Shrimp cultivation and the high work ethic of the cultivator community in carrying out cultivation as well as economic encouragement in running a shrimp farming business to meet family needs, while the inhibiting factor of activities is still the lack of assistance and training in shrimp farming in improving human resources in Majjanang Village